Abundance and Growth of Mole Crab on The Sandy Beach of Tial Village, Central Maluku - Hartono Nurlette; Saiful Alimudi; Nunun Ainun Putri Sari Banun Kaliky (Sam Ratulangi University, 2025)
Sandy beaches are environments that have various biota with remarkable diversity and economic and ecological benefits. One of the sandy beach biotas is the mole crab, which is evenly distributed in Indonesia with diverse types and different characteristics. This study aimed to determine the growth and abundance of mole crabs on sandy beaches in Tial State, Central Maluku. Traditionally, sampling was performed by sweeping the soles of the feet. The entire sample amounted to 49 species and was then analyzed to describe the area's growth and abundance of Mole crabs. The study results indicated that the treason length ranged from to 8-44 mm, with the most frequent being in the class interval of 26-31 mm. A strong relationship existed (R2 = 0.9043) between the group's length and weight addition. This means that an increase will follow every increase in the length of the weight of mole crabs. The growth pattern of the mole crabs was allometrically negative. Hippa marmorata's relative abundance is 98%, while Hippa celaeno is 2%. The dominance index (C=0.9600 > 0.5) indicated a dominant species, namely Hippa marmorata. Mole crabs in this area also had low diversity (H'=0.0996 < 1) and a small population uniformity index (e=0.1437 < 0.4). Keywords: dominance, diversity, evenness, mole crab, length-weight Abstrak Pantai berpasir merupakan lingkungan yang memiliki berbagai biota dengan keanekaragaman yang luar biasa dan memiliki manfaat ekonomi dan ekologi. Salah satu biota pantai berpasir adalah mole crab yang tersebar merata di Indonesia dengan jenis yang beragam dan karakteristik yang berbeda. Penelitian ini bertujuan untuk mengetahui pertumbuhan dan kelimpahan mole crab di pantai berpasir di Negeri Tial, Maluku Tengah. Pengambilan sampel dilakukan secara tradisional dengan menyapu telapak kaki. Keseluruhan sampel berjumlah 49 spesies dan kemudian dianalisis untuk menggambarkan pertumbuhan dan kelimpahan di daerah tersebut. Hasil penelitian menunjukkan bahwa panjang mole crab berkisar antara 8-44 mm, dengan yang paling banyak ditemukan pada interval kelas 26-31 mm. Terdapat hubungan yang kuat (R2 = 0,9043) antara pertambahan panjang dan berat kelompok. Artinya, setiap pertambahan panjang akan diikuti oleh pertambahan berat kepiting bakau. Pola pertumbuhan kepiting mole secara allometrik negatif. Kelimpahan relatif Hippa marmorata sebesar 98%, sedangkan Hippa celaeno sebesar 2%. Indeks dominansi (C=0.9600 > 0.5) menunjukkan adanya spesies yang dominan, yaitu Hippa marmorata. Mole crab di daerah ini juga memiliki keanekaragaman yang rendah (H'=0,0996 < 1) dan indeks keseragaman populasi yang kecil (e=0,1437 < 0,4). Kata kunci: dominansi, keanekaragaman, kemerataan, undur-undur, panjang-bobot